2015
DOI: 10.14814/phy2.12325
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic preconditioning delays the onset of acute mountain sickness in normobaric hypoxia

Abstract: Acute mountain sickness (AMS) is a neurological disorder occurring when ascending too fast, too high. Remote ischemic preconditioning (RIPC) is a noninvasive intervention protecting remote organs from subsequent hypoxic damage. We hypothesized that RIPC protects against AMS and that this effect is related to reduced oxidative stress. Fourteen subjects were exposed to 18 hours of normoxia (21% oxygen) and 18 h of normobaric hypoxia (12% oxygen, equivalent to 4500 m) on different days in a blinded, randomized or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
(97 reference statements)
1
19
0
Order By: Relevance
“…Together, these findings suggest that preconditioning might offer a degree of protection against the onset of high-altitude pulmonary oedema. In addition, RIPC has also been linked to reduced oxidative stress and lower symptoms of acute mountain sickness after acute exposure to normobaric hypoxia (Berger et al 2015a); however, these findings were observed only transiently (0-12 h). After a brief period of no observable protection, a second delayed window of protection appears after ß18-20 h and lasts for 1-2 days (Pérez-Pinzón, 2004;Koch et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these findings suggest that preconditioning might offer a degree of protection against the onset of high-altitude pulmonary oedema. In addition, RIPC has also been linked to reduced oxidative stress and lower symptoms of acute mountain sickness after acute exposure to normobaric hypoxia (Berger et al 2015a); however, these findings were observed only transiently (0-12 h). After a brief period of no observable protection, a second delayed window of protection appears after ß18-20 h and lasts for 1-2 days (Pérez-Pinzón, 2004;Koch et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…After a brief period of no observable protection, a second delayed window of protection appears after ß18-20 h and lasts for 1-2 days (Pérez-Pinzón, 2004;Koch et al 2014). Although clinical outcomes as a result of RIPC seem promising (Thielmann et al 2013), only a very limited number of studies have investigated RIPC and potential further protection against hypoxia (Foster et al 2011(Foster et al , 2014Berger et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…25 Although the latter effects are systemic and may affect virtually any organ, 17,18,26 other benefits of RIPC may extend to processes such as fracture healing, fibrotic prevention, acute mountain sickness, exercise performance, or pancreatitis. 18,[27][28][29][30] On the contrary, the variety of potential action mechanisms may pose limits to the clinical application of RIPC. Commonly used anesthetics/analgesics (eg.…”
mentioning
confidence: 99%
“…Recent study [76] demonstrates that RIPC (four cycles of lower limb ischemia (5 min) and 5 min of reperfusion) transiently reduces symptoms of acute mountain sickness. However, Lalonde [77] investigating the effect of the same RIPC regimen on anaerobic performance in healthy participants, concluded that remote ischemic preconditioning does not offer any significant benefits for anaerobic performance.…”
Section: Clinical Applications Of Ripc In Cardiac Surgerymentioning
confidence: 99%